2010
DOI: 10.1021/je100789k
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Indices and Isentropic Compressibilities of Glycylglycine−FeCl2 in Aqueous Ethanol Mixtures

Abstract: The density and refractive index studies have been carried out for glycylglycine-FeCl 2 in aqueous ethanol mixtures at four different temperatures in the range T ) (288.15 to 318.15) K. A comparative study of the refractive indices obtained experimentally and those calculated by means of Gladstone-Dale and Lorentz-Lorenz relation has been made. Among them, the Gladstone-Dale equation afforded similar values to those obtained experimentally. Isentropic compressibilities, κ S , and excess molar isentropic compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The denaturation of a protein in different aqueous solutions containing salts is an important behavior of biological molecules and has been the subject of extensive investigation. However, the complex configurational and conformational aspects of protein structure in aqueous solution, make it very difficult to directly interpret various biological processes with salts. In recent years, it is recognized that the physicochemical investigations of aqueous solutions containing amino acids or small peptides are of considerable importance and will be helpful in the fundamental understanding of denaturation and other complicated biological processes. Among these technologies, volumetric studies , can provide some unique information in terms of ligand-binding properties, as well as the folding/unfolding character and conformational stability of a globular protein. , …”
Section: Introductionmentioning
confidence: 99%
“…The denaturation of a protein in different aqueous solutions containing salts is an important behavior of biological molecules and has been the subject of extensive investigation. However, the complex configurational and conformational aspects of protein structure in aqueous solution, make it very difficult to directly interpret various biological processes with salts. In recent years, it is recognized that the physicochemical investigations of aqueous solutions containing amino acids or small peptides are of considerable importance and will be helpful in the fundamental understanding of denaturation and other complicated biological processes. Among these technologies, volumetric studies , can provide some unique information in terms of ligand-binding properties, as well as the folding/unfolding character and conformational stability of a globular protein. , …”
Section: Introductionmentioning
confidence: 99%
“…From the above studies, it is clear that no earlier reports on {(glycylglycine + ZnCl 2 ) aqueous methanol} mixtures are available which can give valuable information on solute-solvent interactions and hydrogen bonding within the studied system. Hence, in continuation of our earlier works [18][19][20][21][22][23][24], we report in this paper the excess molar volumes (V E ), viscosity deviations (Dg), deviations in isentropic compressibility (Dj S ) and excess molar refractive indices ðDR E m Þ for {(glycylglycine + ZnCl 2 ) in aqueous methanol} mixtures under diverse conditions. …”
Section: Introductionmentioning
confidence: 58%
“…Some salts tend to disrupt protein structures whereas others protect them . Many studies of thermodynamic properties of protein model compounds have been carried out in aqueous alkali metal and alkaline earths halide solutions. Santosh et al have studied the thermodynamic properties of glycylglycine in aqueous FeCl 2 , MnCl 2 , NiCl 2 , and Mn­(COOCH 3 ) 2 solutions and found that cation and anion play a significant role in influencing the behavior of glycylglycine. In Venkatesu et al’s study, salt effects of KCl, KBr, and KAc on the peptide backbone unit were investigated by transfer free energies .…”
Section: Introductionmentioning
confidence: 99%